Integrated Marketing Communication in Building Online Communities: A Strategic Analysis of Mataharikita.co - Feby Nelson; Christabella Clarissa; Kanienda Geminar (CV. ITTC INDONESIA, 2026)
This article examines the role of Integrated Marketing Communication (IMC) in enhancing the visibility, trust, and sustainability of youth-led non-governmental organizations (NGOs) in Indonesia, with a case study of Mataharikita.co. As a youth organization dedicated to mental health, self-development, and free counseling services, Mataharikita.co faces both opportunities and challenges in engaging stakeholders and sustaining its programs. Using the qualitative research through the thematic analysis,, the study employed semi-structured interviews with organizational members and non-participant observation to explore how IMC strategies are implemented. The researchers analyzed the data by directly linking the information obtained from in-depth interviews to specific pre-existing theories. The data was categorized and assessed based on its relevance to the Integrated Marketing Communication (IMC) framework, specifically examining tools such as advertising, sales promotion, public relations, and direct marketing. The findings reveal that Mataharikita.co relies heavily on Instagram to build a strong online community of more than 13,800 followers through consistent posting, interactive features, and organic engagement. Making Instagram as a central communication platform, Trust-based Public relations, Free Service and Sales Promotion. The study concludes that IMC provides an effective framework for youth NGOs to integrate, also as the contribution of trust-based IMC Model for NGOs, for balancing altruistic missions with organizational sustainability.